2013
DOI: 10.1371/journal.pone.0073660
|View full text |Cite
|
Sign up to set email alerts
|

β-Diversity of Functional Groups of Woody Plants in a Tropical Dry Forest in Yucatan

Abstract: Two main theories have attempted to explain variation in plant species composition (β-diversity). Niche theory proposes that most of the variation is related to environment (environmental filtering), whereas neutral theory posits that dispersal limitation is the main driver of β-diversity. In this study, we first explored how α- and β-diversity of plant functional groups defined by growth form (trees, shrubs and lianas, which represent different strategies of resource partitioning), and dispersal syndrome (aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 78 publications
6
39
1
3
Order By: Relevance
“…To our knowledge, this is the first study to assess changes in the diversity and composition of a metacommunity of secondary forests during succession [61], [62], [63]. Our data show that an important part of the compositional variation across the metacommunity of secondary forests in the Agua Salud area is structured along a successional gradient, with early successional sites that are compositionally more similar to each other than to later successional sites and vice versa.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, this is the first study to assess changes in the diversity and composition of a metacommunity of secondary forests during succession [61], [62], [63]. Our data show that an important part of the compositional variation across the metacommunity of secondary forests in the Agua Salud area is structured along a successional gradient, with early successional sites that are compositionally more similar to each other than to later successional sites and vice versa.…”
Section: Discussionmentioning
confidence: 91%
“…These six species had resprouted, which allowed their rapid recovery after clearing. Other studies in SDTF have shown that resprouting is a common and effective mechanism of regeneration (Ewel, 1980;Murphy and Lugo, 1986;Negreros-Castillo and Hall, 2000;Kennard, 2002;McLaren and McDonald, 2003;Sampaio et al, 2007;López-Martínez et al, 2013). Another study, in gaps caused by similar disturbances, found that 81% of the species had resprouted within 14 months after cutting stems of dbh >2 cm (McLaren and McDonald, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…The ability of species to maintain themselves as part of a new stand also depends on individual structural characteristics and competitive capacities (Yih et al, 1991;Williams-Linera et al, 1997Gaudet and Kaedy, 1988;Vandermeer et al, 2000;Dupuy et al, 2012;López-Martínez et al, 2013). Floristic composition is influenced by the nature of the disturbance (magnitude, frequency and intensity) and the condition of a community when the disturbance occurs (Kellman, 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), but other factors such as individual (meta)population dynamics, herbivore–plant interactions, or strongly autocorrelated biophysical phenomena may be involved (López‐Martínez et al. ).…”
Section: Discussionmentioning
confidence: 99%